Pediatric and Neonatal Surgery - Baerg, Joanne (IntechOpen, 2017)
Neonatal and Pediatric Surgery is a broad field with many challenges. The aim of this short book is to provide the reader with several informative chapters in the field of neonatal and pediatric surgery. Each chapter provides details on a specific area of this changing field. The scope of this book focuses on a few areas that are rare and challenging. For example, it covers preoperative and postoperative care of neonates. Important anesthesia considerations, including anesthesia for neonates and regional anesthesia, are discussed. A unique chapter on neonatal tumors is presented. The book provides an overview of the recent recommendations for care of infants and children that undergo cardiac surgery. The challenging aspects of caustic ingestion are explained. Each chapter stands alone as a detailed source of information for the reader. This book brings updated information with structured headings that will allow the reader to remain focused as the material is reviewed.